PELATIHAN DAN PENDAMPINGAN KEWIRAUSAHAAN: PRODUKSI JAJE BEGINA DI KECAMATAN BLAHBATUH - Luh Gede Kusuma Dewi; Nyoman Ayu Wulan Trisna Dewi; Made Arie Wahyuni (JURNAL SEWAKA BHAKTI, 2022)
Based on the results of observations and interviews, the majority of youth in Blahbatuh District are still students, who will soon complete their studies and will return to the community as part of the economic driver. This is where their concern is to look for other job opportunities, for example good entrepreneurship. Bali is an area with a strong cultural heritage. So far, it can be seen that the influence of the times has made people forget their own culture. At that time, every family helped each other to make jaje gine as a piodalan preparation. but nowadays, jaje gine can be bought easily in the market. Therefore, the cultural tradition of producing jaje upakara is revived through community service programs. The activity was carried out for two days, attended by 15 participants. The results showed that the participants participated enthusiastically and understood the material that had been given.